U.S. citizenship - Gagliardi, Jennifer (--For dummies., 2022)
In this book, expert citizenship and ESL instructor Jennifer Gagliardi walks you through the ins and outs of the complicated process of obtaining citizenship in the United States. From preparing for test day to understanding the interview process and learning about recent changes to immigration laws, this book demystifies the legal process of transforming a foreign national into a citizen of the U.S. You will get up-to-date information on the various application and immigration forms you will need to complete to become a citizen, needed preparation for the all-important interview, and complete coverage of the different visas and green cards available to foreign nationals and how you can qualify for them. Whether you are an immigrant-to-be who is interested in becoming an American citizen, or you are already a citizen but you want to bone up on U.S. history, government, and civics knowledge, this is the perfect guide to the procedural and substantive knowledge you need to understand the American immigration system.